PERANAN PEMBIMBING KEMASYARAKATAN BALAI PEMASYARAKATAN DALAM SISTEM PERADILAN PIDANA ANAK (SPPA) - Luturkey, Onimory; Petrus Irwan Panjaitan; Yuni Artha Manalu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Children in Conflict with the Law Children in conflict with the law are children who are 12 years old but not yet 18 years old who are suspected of committing a crime. The parties involved in the juvenile criminal justice process are Investigators, Public Prosecutors, Judges, and Community Counselors. Correctional center, hereinafter referred to as BAPAS, is a correctional technical implementation unit under the Directorate General of Corrections, Ministry of Law and Human Rights of the Republic of Indonesia which carries out the duties and functions of community research (litmas), guidance, supervision and assistance. Correctional center, hereinafter referred to as BAPAS, is a correctional technical implementation unit under the Directorate General of Corrections, Ministry of Law and Human Rights of the Republic of Indonesia which carries out the duties and functions of community research (litmas), guidance, supervision and assistance..